2014
DOI: 10.1016/j.yjmcc.2014.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-specific expression of CRNK, the C-terminal domain of PYK2, maintains ventricular function and slows ventricular remodeling in a mouse model of dilated cardiomyopathy

Abstract: Rationale Up-regulation and activation of PYK2, a member of the FAK family of protein tyrosine kinases, is involved in the pathogenesis of left ventricular (LV) remodeling and heart failure (HF). PYK2 activation can be prevented by CRNK, the C-terminal domain of PYK2. We previously demonstrated that adenoviral-mediated CRNK gene transfer improved survival and LV function, and slowed LV remodeling in a rat model of coronary artery ligation-induced HF. Objective We now interrogate whether cardiomyocyte-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Analysis of upstream signaling pathways revealed that a sustained increase in intracellular Ca 2+ through Orai1 is associated with Pyk2 (a member of the FAK family of protein tyrosine kinases)/MEK/ERK signaling pathway overactivation. This is consistent with upregulation and activation of Pyk2 in the pathogenesis of LVremodeling and HF [41][42][43] and corroborates that in vitro Orai1 silencing or inhibition has been associated with a reduction of ERK1/2 and Pyk2 activity after phenylephrine treatment in neonatal cardiomyocytes 4 and in glioma cells. 44 In addition, cumulative evidence suggests that Pyk2 and ERK1/2 negatively regulate SER-CA2a expression in neonatal, HL-1, and adult cardiomyocytes, 21,23,[45][46][47] and arterial smooth muscle.…”
Section: Original Research Articlesupporting
confidence: 86%
“…Analysis of upstream signaling pathways revealed that a sustained increase in intracellular Ca 2+ through Orai1 is associated with Pyk2 (a member of the FAK family of protein tyrosine kinases)/MEK/ERK signaling pathway overactivation. This is consistent with upregulation and activation of Pyk2 in the pathogenesis of LVremodeling and HF [41][42][43] and corroborates that in vitro Orai1 silencing or inhibition has been associated with a reduction of ERK1/2 and Pyk2 activity after phenylephrine treatment in neonatal cardiomyocytes 4 and in glioma cells. 44 In addition, cumulative evidence suggests that Pyk2 and ERK1/2 negatively regulate SER-CA2a expression in neonatal, HL-1, and adult cardiomyocytes, 21,23,[45][46][47] and arterial smooth muscle.…”
Section: Original Research Articlesupporting
confidence: 86%
“…FG-3149 had no effect on PKCε expression in either FVB or PKCε mice (Online Figure III). FG-3149 also significantly increased (rather than decreased) the enhanced myofilament phosphorylation of cTnI at Thr143 observed in PKCε mice [23], and had no effect on the modestly increased phosphorylation of MyBP-C at Ser302 (Online Figure IV) [24,25]. Nevertheless, the mAb had significant effects in terms of preserving LV function in PKCε mice.…”
Section: Resultsmentioning
confidence: 99%
“…Myocyte fragments were isolated from frozen LV tissue by mechanical dissociation and chemically permeabilized with 0.3% Triton X-100 and used as described (2,4,22). Active force development was fit to a modified Hill equation that yields maximum force development, Hill coefficient (a measure of cooperativity), and pCa 50 (Ϫlog [Ca 2ϩ ], where 50% of maximum force is developed, a measure of myofilament Ca 2ϩ sensitivity).…”
Section: Methodsmentioning
confidence: 99%